A stochastic model for the throughput analysis of passing dual yard cranes. (November 2017) - Saini, Suruchika; Roy, Debjit; de Koster, René
Highlights: Developed a two-level stochastic model to analyze dual crane performance. Developed a closed-form expression to estimate crane throughput capacity. Developed an approximate approach for estimating crane throughput times. Transaction mix does not affect throughput of cranes in a balanced stack block. Abstract: New container terminal technologies such as passing dual yard cranes per stack promise increase in stacking throughput capacity. However, dual yard cranes can interfere, which reduces the cranes' throughput capacity. Using crane operational protocols, we develop a stochastic model for two passing dual yard cranes and obtain closed-form expressions for the crane throughput capacity with interference delays. We then develop an approximate model to estimate the expected throughput times for both balanced and unbalanced stack configuration. A detailed discrete-event simulation is built to validate the analytical model. We show that interference effects between the cranes can reduce the crane throughput capacity by an average of 35% and interference delays increase with an increase in the number of bays in the stack. We use the model to develop operational insights.